Endometriosis classification, staging and reporting systems: a review on the road to a universally accepted endometriosis classification,. Issue 4 (22nd October 2021) - ,; Vermeulen, Nathalie; Abrao, Mauricio S; Einarsson, Jon I; Horne, Andrew W; Johnson, Neil P; Lee, Ted T M; Missmer, Stacey; Petrozza, John; Tomassetti, Carla; Zondervan, Krina T; Grimbizis, Grigoris; et al.
Abstract: STUDY QUESTION: Which endometriosis classification, staging and reporting systems have been published and validated for use in clinical practice? SUMMARY ANSWER: Of the 22 endometriosis classification, staging and reporting systems identified in this historical overview, only a few have been evaluated, in 46 studies, for the purpose for which they were developed. WHAT IS KNOWN ALREADY: In the field of endometriosis, several classification, staging and reporting systems have been developed. PARTICIPANTS/MATERIALS, SETTING, METHODS: A systematic PUBMED literature search was performed. Data were extracted and summarized. MAIN RESULTS AND THE ROLE OF CHANCE: Twenty-two endometriosis classification, staging and reporting systems have been published between 1973 and 2021, each developed for specific, and different, purposes. There still is no international agreement on how to describe the disease. Studies evaluating the different systems are summarized showing a discrepancy between the intended and the evaluated purpose, and a general lack of validation data confirming a correlation with pain symptoms or quality of life for any of the current systems. A few studies confirm the value of the ENZIAN system for surgical description of deep endometriosis. With regards to infertility, the endometriosis fertility index has been confirmed valid for its intended purpose. LARGE SCALE DATA: NA. LIMITATIONS, REASONS FOR CAUTION: The literature search was limited to PUBMED. Unpublished classification, staging or reporting systems, or those published in books were not considered. WIDER IMPLICATIONS OF THE FINDINGS: It can be concluded that there is no international agreement on how to describe endometriosis or how to classify it, and that most classification/staging systems show no or very little correlation with patient outcomes. This overview of existing systems is a first step in working toward a universally accepted endometriosis classification. STUDY FUNDING/COMPETING INTEREST(S): The meetings and activities of the working group were funded by the American Association of Gynecologic Laparoscopists, European Society for Gynecological Endoscopy, European Society of Human Reproduction and Embryology and World Endometriosis Society. A.W.H. reports grant funding from the MRC, NIHR, CSO, Wellbeing of Women, Roche Diagnostics, Astra Zeneca, Ferring, Charles Wolfson Charitable Trust, Standard Life, Consultancy fees from Roche Diagnostics, AbbVie, Nordic Pharma and Ferring, outside the submitted work. In addition, A.W.H. has a patent Serum biomarker for endometriosis pending. N.P.J. reports personal fees from Abbott, Guerbet, Myovant Sciences, Vifor Pharma, Roche Diagnostics, outside the submitted work; he is also President of the World Endometriosis Society and chair of the trust board. S.M. reports grants and personal fees from AbbVie, and personal fees from Roche outside the submitted work. C.T. reports grants, non-financial support and other from Merck SA, non-financial support and other from Gedeon Richter, non-financial support from Ferring Pharmaceuticals, outside the submitted work and without private revenue. K.T.Z. reports grants from Bayer Healthcare, MDNA Life Sciences, Roche Diagnostics Inc, Volition Rx, outside the submitted work; she is also a Board member (Secretary) of the World Endometriosis Society and World Endometriosis Research Foundation, Research Advisory Board member of Wellbeing of Women, UK (research charity), and Chair, Research Directions Working Group, World Endometriosis Society. The other authors had nothing to disclose. TRIAL REGISTRATION NUMBER: NA.